(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The psychological meaning of this remark is not only that with a change in the way of satisfying a need, the need itself changes, but also that the sociocultural transformation of a natural phenomenon inevitably creates a specific area of cultural norm and pathology, the laws of which cannot be deduced from an organic substrate. Despite such an important place occupied by human sexuality, it relatively rarely became the subject of psychological research proper, and the insufficient methodological elaboration of the issue also had an effect.